2008
DOI: 10.1038/bjp.2008.335
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid amide hydrolase produces PPAR‐α‐mediated analgesia in a rat model of inflammatory pain

Abstract: Background and purpose:We have previously demonstrated antinociceptive effects of fatty acid amide hydrolase (FAAH) inhibition that were accompanied by increases in the levels of endocannabinoids (ECs) in the hind paw. Here, the effects of the FAAH inhibitor URB597 (3 0 -carbamoyl-biphenyl-3-yl-cyclohexylcarbamate) on responses of spinal neurons were studied. Experimental approach: Extracellular single-unit recordings of dorsal horn neurons were made in anaesthetized rats with hind paw inflammation induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 49 publications
(80 reference statements)
2
63
0
Order By: Relevance
“…In contrast, although this hypothesis could not be tested in the present study, the fact that the effects of URB597 were reversed by the CB 1 antagonist/inverse agonist rimonabant may indicate that selective activation of CB 1 receptors can produce synergistic effects with PPAR-a. These results are consistent with recent findings that joint stimulation of PPAR-a and CB 1 receptors produces synergistic antinociceptive effects on peripheral pain, that these effects are reversed by rimonabant (Russo et al 2007), and that antinociceptive effects of URB597 on peripheral pain can be blocked by PPAR-a antagonism (Sagar et al 2008). Further studies are needed to determine whether synergistic enhancement of learning and memory can be achieved with local coadministration of naturally occurring endogenous ligands for CB 1 receptors (anandamide) and PPAR-a (OEA and PEA), whose brain levels are all increased by FAAH inhibition.…”
supporting
confidence: 93%
“…In contrast, although this hypothesis could not be tested in the present study, the fact that the effects of URB597 were reversed by the CB 1 antagonist/inverse agonist rimonabant may indicate that selective activation of CB 1 receptors can produce synergistic effects with PPAR-a. These results are consistent with recent findings that joint stimulation of PPAR-a and CB 1 receptors produces synergistic antinociceptive effects on peripheral pain, that these effects are reversed by rimonabant (Russo et al 2007), and that antinociceptive effects of URB597 on peripheral pain can be blocked by PPAR-a antagonism (Sagar et al 2008). Further studies are needed to determine whether synergistic enhancement of learning and memory can be achieved with local coadministration of naturally occurring endogenous ligands for CB 1 receptors (anandamide) and PPAR-a (OEA and PEA), whose brain levels are all increased by FAAH inhibition.…”
supporting
confidence: 93%
“…The demonstration that, at least in cells, 15-LOX is capable of metabolizing 2-AG to 15-HETE-G (see references in Vandevoorde & Lambert [112]), which is a ligand for the antiinflammatory nuclear receptor PPARa [28], suggests that changes in LOX expression and metabolism of endocannabinoids via this pathway may also influence nociceptive processing. Indeed, we and others have shown that PPARa ligands can have marked inhibitory effects on inflammatory pain responses (see references in [113][114][115][116]). …”
Section: Effects Of Novel Biological Metabolites Of 2-ag and Anandamidementioning
confidence: 91%
“…Systemic inactivation of FAAH via compounds such as URB597, OL135 and PF-3845 has been shown to be anti-nociceptive in models of acute and inflammatory pain (75)(76)(77)(78)(79)(80) . Elevations in both AEA and 2-AG have been shown, as well as reduced carrageenan-induced hyperalgesia (81) and expansion of peripheral receptive field size of wide dynamic range neurons (a marker of central sensitisation) following intra-plantar URB597 (82) . Similarly, capsaicin-induced pain behaviour and thermal hypersensitivity were attenuated following blockade of peripheral MAGL via JZL184 (83) , and peripheral administration of JZL184 produces local inhibition of MAGL activity, increased levels of 2-AG and anti-nociceptive effects in both phases of the formalin model through mechanisms involving both CB 1 and CB 2 ( 84) .…”
Section: Peripheral Mechanismsmentioning
confidence: 99%